I Am So Upset About Everything! An Interactive Web-Based Case - Derrick Akira Hamaoka; Matthew Goldenberg (Association of American Medical Colleges, 2013)
Abstract A patient with anxiety is not something every third-year will see while on rotation, but the case is an important one to have exposure to. This 30-minute, web-based exercise, created in SoftChalk, features a patient with an anxiety disorder. The case provides history of present illness, background history, and mental status examination. As the case progresses, knowledge checks are presented for the student to answer, and feedback is provided. The exercise also discusses the differential diagnosis, treatment, and prognosis of a particular anxiety disorder, then concludes with additional test questions. The exercise has been used as an independent learning tool that supplements preclinical medical student lectures on anxiety disorders and stress. It could be adapted for small-group settings and preceptor-guided sessions in order to better emphasize the psychiatric history, mental status examination, differential, and treatment modalities.